RIGI, TLR7, and TLR3 Genes Were Predicted to Have Immune Response Against Avian Influenza in Indigenous Ducks - Pal, Aruna; Pal, Abantika; Baviskar, Pradyumna (Frontiers in Molecular Biosciences, 2021)
Avian influenza is a disease with every possibility to evolve as a human-to-human pandemic arising out of frequent mutations and genetic reassortment or recombination of avian influenza (AI) virus. The greatest concern is that till date, no satisfactory medicine or vaccines are available, leading to massive culling of poultry birds, causing huge economic loss and ban on export of chicken products, which emphasizes the need to develop an alternative strategy for control of AI. In the current study, we attempt to explore the molecular mechanism of innate immune potential of ducks against avian influenza. In the present study, we have characterized immune response molecules such as duck TLR3, TLR7, and RIGI that are predicted to have potent antiviral activities against the identified strain of avian influenza through in silico studies (molecular docking) followed by experimental validation with differential mRNA expression analysis. Future exploitation may include immunomodulation with the recombinant protein, and transgenic or gene-edited chicken resistant to bird flu.